Expression of apoptosis repressor with caspase recruitment domain (ARC) in familial adenomatous polyposis (FAP) adenomas and its correlation with DNA mismatch repair proteins, p53, Bcl-2, COX-2 and beta-catenin - Roser, Christoph; Tóth, Csaba; Renner, Marcus; Herpel, Esther; Schirmacher, Peter (Cell communication and signaling, 2021)
Colorectal familial adenomatous polyposis (FAP) adenomas exhibit a uniform pathogenetic basis caused by a germline mutation in the adenomatous polyposis gene (APC), but the molecular changes leading to their development are incompletely understood. However, dysregulated apoptosis is known to substantially affect the development of colonic adenomas. One of the key regulatory proteins involved in apoptosis is apoptosis repressor with caspase recruitment domain (ARC).